10d+16=12d-6

Simple and best practice solution for 10d+16=12d-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10d+16=12d-6 equation:


Simplifying
10d + 16 = 12d + -6

Reorder the terms:
16 + 10d = 12d + -6

Reorder the terms:
16 + 10d = -6 + 12d

Solving
16 + 10d = -6 + 12d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-12d' to each side of the equation.
16 + 10d + -12d = -6 + 12d + -12d

Combine like terms: 10d + -12d = -2d
16 + -2d = -6 + 12d + -12d

Combine like terms: 12d + -12d = 0
16 + -2d = -6 + 0
16 + -2d = -6

Add '-16' to each side of the equation.
16 + -16 + -2d = -6 + -16

Combine like terms: 16 + -16 = 0
0 + -2d = -6 + -16
-2d = -6 + -16

Combine like terms: -6 + -16 = -22
-2d = -22

Divide each side by '-2'.
d = 11

Simplifying
d = 11

See similar equations:

| 7y+3=8y-3 | | -14=y/10 | | 7n+6n-5=-6(m+7) | | ln(x)=0.28 | | 9m-3=6m+6 | | 9/15=a/5 | | 6k-24=5K-5 | | y+2x+10=4x+5 | | 11z+86=34z-29 | | 7c-88=4c+11 | | 14/32=49/x | | 24p-7=14p+93 | | 6(2x+3)=9x+3x-8 | | 11b-7=180 | | 10r+61=15r+11 | | 40m-88=28m-16 | | 6(2x-3)=9x-18+3x | | 2(x+1)+2x=4x+2 | | 3a+16=a+46 | | 2(x+9)=54 | | 2x-4=3x+20.4 | | 9n+41=14n-59 | | 2.5x+3x+(2x+3)=60 | | 0.4(10x+15)=2(x+10) | | y=25-16t^2 | | 13g-96=6g-75 | | 0.2(25x-20)=5x+6 | | 13s+21=16s-12 | | X^3+6x^2+8x=480 | | 2b+5=180 | | 4s+80=8s-32 | | 0.2(15x+20)=3x+4 |

Equations solver categories